2015
DOI: 10.1002/star.201400251
|View full text |Cite
|
Sign up to set email alerts
|

Effect of wet ball milling on physicochemical properties and crosslinking reaction performance of corn starch

Abstract: Corn starch was physically modified with a ball mill in ethanol. The effect of ball-milling treatment on particle morphology, particle size distribution, crystalline structure, and pasting property was examined by means of scanning electron microscopy (SEM), laser diffractometer, X-ray diffraction (XRD), and rapid viscosity analyzer (RVA). In addition, the ball-milling effect on crosslinking performance of corn starch was also investigated. It was observed that the milled starch granules lost surface smoothnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…Lin et al also found the same result for potato starch after 15 days of acid‐alcohol treatment. Samples PS1.5 and PS3 granules showed pie shapes and some granules displayed a few small fissures on the surface, which was in agreement with the previous researches reporting the shape of starch granules treated by ball milling . For the samples PS1.5 and PS3 after 8 days of treatment, small fissures became more obvious and cavity presented inside the starch granule (Figure B2), which was in accordance with the results observed by optical microscope.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Lin et al also found the same result for potato starch after 15 days of acid‐alcohol treatment. Samples PS1.5 and PS3 granules showed pie shapes and some granules displayed a few small fissures on the surface, which was in agreement with the previous researches reporting the shape of starch granules treated by ball milling . For the samples PS1.5 and PS3 after 8 days of treatment, small fissures became more obvious and cavity presented inside the starch granule (Figure B2), which was in accordance with the results observed by optical microscope.…”
Section: Resultssupporting
confidence: 91%
“…Hence, the modification of native starch is necessary to provide adequate functional and physicochemical properties. As a safe and economical physical method, ball milling is widely used to modify starch . The crystallinity degree of starch granules is significant changed under the action of combined shear, friction and collision in the ball milling process .…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical resistance and high energy during milling induced damage to the crystalline structure of starch, increasing the amorphous region and reducing the RC, as observed by Oliveira et al . and Zhang et al …”
Section: Resultssupporting
confidence: 56%
“…The reduction in RC was more pronounced for the double modification. The damage to the starch structure may be converting it into non‐crystalline states . A decrease in the crystallinity of starch corroborated the decrease in enthalpy (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation